Investigation of emulsion and effect on emission in CI engine by using diesel and bio-diesel fuel: A review - Harsh Kapadia; Hardik Brahmbhatt; Yuvrajsinh Dabhi; Sajan Chourasia (Egyptian Journal of Petroleum)
The exhaust of diesel engine is a main significant air pollution source which affects the environment and human life. A number of researchers have contributed their valuable efforts from each and every perspective to reduce air pollution. In the present work in-depth analysis is done on the recent investigation which is carried out in the field of alternative Fuels. The study examines the result of several aspects of emulsion stability and also investigated variables such as type of surfactant, mixing speed, mixing time and various additives and its effect on emission. Higher mixing speed with less water percentage increases emulsion stability. The objective of this paper is to highlight the analysis on W/D emulsion fuel, emulsion fuel stability and effect of W/D fuel on combustion, performance and emission characteristic. The results disclose an enhancement in engine performance and reduction of harmful emission for various additives compared to diesel. Keywords: Emulsification, W/O emulsion, O/W/O emulsion, HLB ratio, Stability, Engine emission